Mineral and water content of A-gigas scales determine local micromechanical properties and energy dissipation mechanisms - Troncoso, OP (2017)
The authors would like to thank the Vice-Rectorate for Research (VRI) of the Pontificia Universidad Catolica del Peru for financial support. They would like to thank The National Council of Science, Technology and Technological Innovation (CONCYTEC) for financial support.